One‐step deep eutectic solvent strategy for efficient analysis of aflatoxins in edible oils. (13th July 2020) - He, Tingting; Zhou, Tong; Wan, Hao; Han, Quanbin; Ma, Yaqian; Tan, Ting; Wan, Yiqun
Abstract: BACKGROUND: Aflatoxins, a kind of carcinogen, have attracted increasing attention due to their toxicity and harmfulness to human health. Traditional methods for aflatoxins analysis usually involve tedious extraction steps with a subsequent derivatization process. Herein, a simple and efficient liquid‐phase microextraction method based on deep eutectic solvents (DESs) for direct analysis of aflatoxins was developed. RESULTS: Adopting DESs as the extractant, we surprisingly found out that DESs could either achieve good extraction performance or play a similar role to the derivatization agent, achieving an enhancement of fluorescence intensity for direct analysis of aflatoxins by high‐performance liquid chromatography combined with fluorescent detection. Under optimal conditions obtained by response surface methodology, the method provided satisfactory linear ranges (0.01–0.75 μg kg −1 for AFB1 and AFG1, 0.003–0.25 μg kg −1 for AFB2 and AFG2) with good determination coefficients ( R 2 > 0.9988), a low detection limit (0.0005–0.003 μg kg −1 ), and good recovery rates (72.05–113.54%). CONCLUSION: These results highlighted superiorities of the one‐step DES strategy for analysis of aflatoxins in edible oils, providing insights for future development of efficient methods in food analysis. © 2020 Society of Chemical Industry